2020
DOI: 10.21037/atm.2020.01.37
|View full text |Cite
|
Sign up to set email alerts
|

Novel prognostic nomograms for female patients with breast cancer and bone metastasis at presentation

Abstract: Background: There is a paucity of literature about prognostic evaluation for patients with breast cancer (BC) and bone metastasis at presentation. To date, little is known about how to accurately predict the prognosis of BC patients with bone metastasis at presentation. Thus, an accurate prediction tool of prognosis in this population is urgently needed. Our goal is to construct novel and prognostic nomograms for BC patients with bone metastasis at presentation. Methods:We searched Surveillance, Epidemiology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
4
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 49 publications
7
54
4
6
Order By: Relevance
“…The result of our study also showed that surgical treatment could significantly reduce the cancer‐specific risk of death in BMC patients, which is consistent with the clinical experience of most doctors. Some scholars included chemotherapy and radiotherapy in their studies by SEER database (Du et al, 2020; Han et al., 2020; Wang, Cheng, et al, 2020; Wang, Wu, et al, 2020). However, the latest statement of SEER database (https://seer.cancer.gov/data/ChemotherapyRadiation-SEER-DUA.pdf) said that because the staff could not correctly distinguish whether patients received radiotherapy or chemotherapy when collecting data, they did not recommend the above two variables to be used in the analysis of relationship between treatment and patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of our study also showed that surgical treatment could significantly reduce the cancer‐specific risk of death in BMC patients, which is consistent with the clinical experience of most doctors. Some scholars included chemotherapy and radiotherapy in their studies by SEER database (Du et al, 2020; Han et al., 2020; Wang, Cheng, et al, 2020; Wang, Wu, et al, 2020). However, the latest statement of SEER database (https://seer.cancer.gov/data/ChemotherapyRadiation-SEER-DUA.pdf) said that because the staff could not correctly distinguish whether patients received radiotherapy or chemotherapy when collecting data, they did not recommend the above two variables to be used in the analysis of relationship between treatment and patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…But, most nomograms are based on the traditional Kaplan–Meier approach and Cox proportional hazard model, ignoring the occurrence of competitive events, thereby misjudged the prognosis of patients. For instance, if a patient died from a cardiovascular disease or accident rather than cancer, and we did not add it to the survival analysis, it would lead to the deviation of the predicted results from the real situation (van Walraven & McAlister, 2016; Wang, Cheng, et al, 2020; Wang, Wu, et al, 2020). A competing risk model (Gray's test and Fine–Gray proportional hazard model) can well deal with the relationship between cancer outcomes and competitive events so that the accuracy of prognosis analysis of cancer patients can be improved significantly (Fine & Gray, 1999; Gray, 1988; Scrucca, Santucci, & Aversa, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The nomograms of OS and CSS are shown in Figures 2 and 3 . Nomogram is a quite user-friendly predictive tool which enables clinician or patient to determine the survival probability by calculating the scores of covariate and then draw a line vertically downward [ 16 ]. The scores assigned to each factor were listed in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have reported on the prediction of metastatic Ewing's sarcoma(MES) models-ROC 6 . But now, nomograms were the graphical description of predictive statistical model, which has been widely used to accurately predict the survival of cancer patients, such as bladder cancer, colon and breast cancer [7][8][9][10][11] . To the best of our knowledge, nomogram have not been used in patients with metastatic ES.…”
Section: Introductionmentioning
confidence: 99%